Homogeneous Grand Mixed Herz–Morrey Spaces and Their Applications - Xiaoxi Xia; Jiang Zhou (Axioms)
In this paper, we introduce the homogeneous grand mixed Herz–Morrey spaces <semantics>M<msubsup><mover accent="true">K˙</mover><mover accent="true">q˜</mover>,λα,p),θ</msubsup>(Rn)</semantics> and investigate their fundamental properties. We further explore the boundedness of sublinear operators and fractional-type operators on these spaces, establishing new results that contribute to the broader understanding of their applications.